ANALISIS MUTU MINUMAN INSTAN BERBAHAN DASAR BUAH MENGKUDU (Morinda citrifolia L) DAN JAHE MERAH (Zingiber officinale rosc) - Andi Citra Islamiah; Husain Syam; Andi Sukainah (Universitas Negeri Makassar, 2022)
This study aims to determine the chemical properties of instant drinks produced and the best concentration by adding noni and red ginger to the manufacture of instant drinks based on organoleptic test results. This research is an experimental study with an experimental design that is used is Factorial Completely Randomized Design (CRD) which consists of two factors, namely the factor A noni fruit, namely: 100 g, 200 g, 300 g. The red ginger B factor is: 75 g, 100 g, 125 g. The chemical analysis results were the highest water content with the addition of 300 g noni fruit concentration 2,8678 and 125 ginger concentration 2,9456, the highest antioxidant activity with the addition of 300 g noni fruit concentration 71,100 and red ginger concentration 125 g 70,0178, and from the alkaloid test all treatments in instant drinks contain positive alkaloids. The results of organoleptic color, aroma and taste are preferred by panelists with the addition of 100 g of noni fruit and the concentration of red ginger 125 g.